VR chemistry - Toh, Benjamin Junhao (Nanyang Technological University, 2022)
Virtual Reality (VR) enhances the user experience through immersive interactions and visualisations. The utilisation of VR in the education sector is an opportunity not to be passed up. The goal of this project is to allow users to load pre-set molecular 3D models and interact and observe them in real time, with the help of VR. An immersive three-dimensional learning environment was implemented and new features of the vrclassroom application were created. Users can load molecules into the application, perform rotations and duplication on the molecules, and view the molecules in the three-dimensional space using a VR headset. This project makes it easier for chemistry educators to teach and students to learn, by incorporating VR technology in a classroom application. The application is developed using Unity and will be run on the computer and a VR headset.